The gatekeeper : narrative voice in Plato's dialogues - Finkelberg, Margalit (Brill's Plato Studies Series, 2019)
In The Gatekeeper: Narrative Voice in Plato's Dialogues Margalit Finkelberg offers the first narratological analysis of all of Plato's transmitted dialogues. The book explores the dialogues as works of literary fiction, giving special emphasis to such topics as narrative levels, focalization, narrative frame, and metalepsis. The main conclusion of the book is that in Plato the plurality of the speakers' opinions is not accompanied by a plurality of points of view. Only one perspective is available, that of the narrator. Contrary to the widespread view, Plato's dialogues cannot be considered multivocal, or "dialogic" in Bakhtin's sense. By skillful use of narrative voice, Plato unobtrusively regulates the readers' reception and response. The narrator is the dialogue's gatekeeper, a filter whose main function is to control how the dialogue is received by the reader by sustaining a certain perspective of it.